PROJECT FOR STRENGTHENING PANCASILA STUDENT PROFILES: BASED ON LOCAL WISDOM AT ELEMENTARY SCHOOL LEVEL - Muyassarah; Utama Rizal, Setria; Gofur, Abdul (Program Studi PGMI, 2025)
The purpose of this research is to describe the Project for Strengthening the Pancasila Student Profile: Based on Local Wisdom at the Elementary School Level. The research method used is qualitative with a Case Study approach. The subject of this study is a Class I C Teacher with an Informant Principal. The data analysis technique uses source triangulation while the data collection technique uses observation, interviews and documentation. Data analysis (Miles, 1994), Data condensation, Data display, drawing and verifying conclusions. The results of this study show that the Pancasila Student Profile Strengthening Project based on local wisdom at SDN 1 Menteng Palangka Raya has been carried out well. The school carries out planning, implementation and evaluation contained in the teaching modules that have been developed so that the theme of local wisdom sub-theme of traditional games has been implemented and is able to support the activity of students at the elementary school level.